Hopera de citraria de falcone pellegrine et gentiled’Alfonso Caracciolo. - FENOLLOSA, ROSER MELCHOR (Scripta, 2021)
We offer the critical edition of a treatise of falconry written in Italian from Calabria. It also has some Catalan features, and it is linked to a number of texts from the library of Naples belonging to the kings of Aragon. This codex from the Royal Library of the Monastery of San Lorenzo de El Escorial, being its identification C-IV-6, contains seven documents. One of these documents is Hopera de citraria de falcone pellegrine et gentile (Treatise of falconry of peregrine falcon and gentle hawk) written by Alfonso Caracciolo, having more than 40 pages. This text follows the tradition of medieval treatise, and it was probably written at the end of the 15th century. The aim of the author is to teach to train peregrine falcons and gentle hawks, even though it has other content related to hunting, and it is based on the author’s experience.